This Prison Where I Live - Bloomstein, Rex (Rex Entertainment Ltd., 2010)
Opposition politician Aung San Suu Kyi is not the last popular figure to languish in a Burmese prison. Zarganar, a stand-up comedian known for his wicked anti-government satire has been imprisoned for 35 years for “public order offenses.” Prior to his incarceration, he had been banned from performing publicly. Still Zarganar, whose stage name means “tweezers,” continued for years to fight Burmese dictatorial suppression with humor. In this film, British filmmaker Rex Bloomstein and German comedian Michael Mittermeier travel to Myanmar to investigate humor under dictatorship and to somehow let Zarganar know he hasn’t been forgotten.